2020
DOI: 10.1016/j.ekir.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Urinary CD80 Discriminates Among Glomerular Disease Types and Reflects Disease Activity

Abstract: Introduction: Heterogeneity of nephrotic diseases and a lack of validated biomarkers limits interventions and reduces the ability to examine outcomes. Urinary CD80 is a potential biomarker for minimal change disease (MCD) steroid-sensitive nephrotic syndrome (NS). We investigated and validated a CD80 enzymelinked immunosorbent assay (ELISA) in urine in a large cohort with a variety of nephrotic diseases. Methods: A commercial CD80 ELISA was enhanced and analytically validated for urine. Patients were from Mayo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(41 reference statements)
3
9
0
Order By: Relevance
“…Our group recently demonstrated that CD80 is indeed present in podocytes in MCD, but, surprisingly, most CD80 was lining the capillary lumens in an endothelial pattern ( 109 ). We and others also showed that urinary CD80 levels are consistently high in a subset of patients with MCD in relapse compared to controls and to patients with other proteinuric glomerular disease ( 68 , 112 115 ). Interestingly, there are two cases reported in that patients with active MCD and high CD80 in urine underwent rapid transient and sustained remission following anti-CD80 therapy, respectively ( 116 , 117 ).…”
Section: Podocyte Dysfunctionsupporting
confidence: 61%
“…Our group recently demonstrated that CD80 is indeed present in podocytes in MCD, but, surprisingly, most CD80 was lining the capillary lumens in an endothelial pattern ( 109 ). We and others also showed that urinary CD80 levels are consistently high in a subset of patients with MCD in relapse compared to controls and to patients with other proteinuric glomerular disease ( 68 , 112 115 ). Interestingly, there are two cases reported in that patients with active MCD and high CD80 in urine underwent rapid transient and sustained remission following anti-CD80 therapy, respectively ( 116 , 117 ).…”
Section: Podocyte Dysfunctionsupporting
confidence: 61%
“…CD80 staining in native and post-transplantation renal biopsies identified a subset of patients with FSGS in whom this mechanism seems to be relevant (74), even though these findings were not corroborated by other groups (75,76). Notably, urinary excretion of CD80 assessed in two large patient cohorts correlated with disease activity and was able to discriminate between primary and secondary FSGS forms, although the highest values were observed for MCD cases (77).…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…However, using multiple methodologies, we could demonstrate de novo expression of CD80 in both glomerular endothelial cells and podocytes in a subset of patients with minimal change disease (Cara-Fuentes et al, 2020). Furthermore, several other groups have also confirmed that urinary CD80 excretion increases markedly in subjects with MCD compared to other proteinuric glomerular diseases, although the clinical significance is yet to be determined (Ahmed et al, 2018;Gonzalez Guerrico et al, 2020;Ling et al, 2015Ling et al, , 2018Mishra et al, 2017). As CD80 is a coregulatory molecule in T cell response, this is consistent with evidence for immune modulation in the glomeruli in MCD (Colucci et al, 2018).…”
Section: Introductionmentioning
confidence: 64%